Purification of wastewater digester biogas from siloxanes via adsorption-desorption with NaOH-reformed SiO2 adsorbent - Jung, Hyounduk; Jurng, Jongsoo (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
This study was performed in order to investigate the adsorption of siloxane for biogas treatment using a novel SiO2-based adsorbent and its regeneration. The siloxane adsorption capacity of the NaOH-modified SiO2 was significantly increased. At low temperature (25-50 degrees C), the siloxane (D5) adsorption capacity of the novel SiO2 adsorbent was 200 mg per g of adsorbent, which is approximately four times than that observed for silica gel or SiO2 prior to treatment with NaOH. The siloxane retention mechanism of silica particles is the influence of the hydrogen bonds formed between the Si-O-Si groups on the siloxane surface and the OH groups on the silica surface. Therefore, increasing the concentration of NaOH used in the reforming step will increase the density of OH group density increased proportionally and siloxane adsorption capacity also increased. The number of OH groups, determined based on the TGA analysis, was increased to 4.7 OH/nm(2) using 3 M NaOH from 1.3 OH/nm(2) of pure SiO2. This also supports the hypothesis that the concentration of OH groups on the SiO2 is proportional to the NaOH concentration. (C) 2020 Published by Elsevier Ltd.
Keywords: REMOVAL; SILICA